THE QUALITY OF CORPORATE GOVERNANCE IN ROMANIA - Alina HAGIU; Marinela BĂRBULESCU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
corporate governance, quality, business environment, performance